ANJAK PIUTANG (TANPA RECOURSE) SEBAGAI SALAH SATU ALTERNATIF UNTUK MENGATASI MASALAH CASH FLOW BAGI UKM DI INDONESIA DAN PERLAKUAN AKUNTANSINYA - Sugiarti, Yenny (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
Small and medium enterprises (SMEs) often face a cash flaw problem due to a difficulty of internal source of fund. In order to obtain external sources, SMEs usually apply for credits from banks. However, the credits require a rigid debt covenant, which often causes a constraint to SMEs in their operational activities. In several countries, factoring is an alternative financing for external sources. This alternative has come to be a favored solution, especially for SMEs. This paper attempts to show the possibility for adopting the factoring, especially a factoring without recourse, in SMEs in Indonesia. In order to support the arguments, the author shows the evidence of the success story in several countries. The author also explains the advantages of factoring without recourse and the accounting treatment of factoring in order to show the advantage in working capital